The case of Philippine stand-alone cinemas and its challenges for the film industry and government - Ordenes, Francis Leo Maria Del Fierro (Animo Repository, 2021)
Film watching can be considered as one of the most popular cultural practices of Filipinos. It has been a part of their lifestyle since the 1940s. Likewise, Manila was once praised for its opulence and luxury; it was a proud playground of the cultured elites whose famous pastimes included watching films in grand cinema houses among others. Such edifices were designed elegantly and adorned intricately by world-renowned architects, making them true symbols of prestige.Unfortunately, the popularity and physical aspects of these stand-alone cinema houses have deteriorated. These are caused by three main factors: dwindling number of moviegoers, digitization, and the presence and continuous development of mall-based cinemas. Most of these stand-alone cinemas have been reduced to an all-time low having been notoriously associated with sordid films and prostitution.This study discusses the reasons behind the decline of stand-alone cinemas in Manila. Primarily, it attempts to explain why, out of the more than 50 pioneer movie houses, only a handful remains today. Why are some still in operation while others have closed? How do they situate themselves amid very stiff competition with mall-based and other contemporary cinemas? Have there been efforts from the government for their sustenance?While locating this research in the general framework of media studies, it attempts to cross-reference it with cultural studies that seeks to account for the history of films, particularly the distribution and exhibition in stand-alone cinemas.This research employed the case study approach. The data were collected through in- depth interviews with officers in charge of both currently functioning and former stand-alonecinemas, and triangulated with heads of government agencies, particularly from the National Commission for Culture and the Arts, as well as non-government and private entities.The results of this study are significant for the owners and the management of stand- alone cinema houses. Both government and non-government organizations may likewise benefitfrom this research by adapting policies to achieve greater conservation in light of uncertainties these stand-alone cinemas are currently facing. More importantly, it hopes to inculcate and ignite one¶V inWeUeVW in VWand-alone cinemas as part of the Filipino heritage.